Fungsi dan sistim pembinaan dunia usaha dalam rangka penanaman modal (Badan Koordinasi Penanaman Modal, 1986)
Description of the functions and relations of the Investment Coordinating Board and other government agencies with reference to administrational procedures for capital investment in Indonesia.